Aujuhu al-Tasyabuhi wa al-Tanahuri Baina al-Lughataini al-Arabiyah wa al-Tamiliyah Ala Mustawa al-Ashwat - Mohammed Cassim Sithy Shathifa (UIN Siber Syekh Nurjati Cirebon, Indonesia, 2020)
Language is every sound the people use to express their ideas and communicate with others. It is the basis of any language. Every language has its own unique systems in phonemic and orthographical symbols. According to this concept, Arabic is a Semitic language whereas Tamil is Indo â€“European language, there is no doubt that it is difficult to foreign language learners to identify the place of articulation of the unfamiliar sounds, its pronunciations and writing format. Among them are the Tamil â€“ speaking Muslims who use and learn Arabic as a foreign language. TheyÂ faceÂ difficulties in pronouncingÂ andÂ writing Arabic letters,Â properÂ nounsÂ andÂ termÂ words dueÂ toÂ theÂ lackÂ ofÂ clarityÂ inÂ the sounds between these two languages. This study try to identify similarities and differences between the sound of Arabic and Tamil languages. This research focus on descriptive and contrastive methods to analyze the data gathered from secondary data such as books and previous studies related to the topic. The result indicates that the Arabic letters are differ from Tamil letters in terms of their number, writing method and their shapes. And also, it has six vowels similar to the six vowels of Tamil language in pronunciation. But they differ in places of articulation and its aspects. Thus, Consonants of Arabic differ from Tamil consonants in pronunciation places of articulation and IPA for them. Consequently, this study will support to determine the pronunciation of Arabic letters and read Arabic language in the best way.Ø¥Ù† Ø§Ù„Ù„ØºØ© Ù‡ÙŠ Ø£ØµÙˆØ§Øª ÙŠØ¹Ø¨Ø± Ø¨Ù‡Ø§ ÙƒÙ„ Ù‚ÙˆÙ… Ø¹Ù† Ø¢Ø±Ø§Ø¦Ù‡Ù… ÙˆØ£ÙÙƒØ§Ø±Ù‡Ù…ØŒ ÙˆÙ‡ÙŠ Ø£Ø¯Ø§Ø© ØªØ³Ø§Ø¹Ø¯ Ø¹Ù„Ù‰ Ø§Ù„Ø§ØªØµØ§Ù„ Ø¨Ø§Ù„Ø¢Ø®Ø±ÙŠÙ†. ÙˆÙƒÙ„ Ù„ØºØ© ØªØªØ±ÙƒØ¨ Ù…Ù† Ø¬ÙˆØ§Ù†Ø¨ Ø£Ø±Ø¨Ø¹Ø© : Ø§Ù„Ø£ØµÙˆØ§ØªØŒ Ø§Ù„ØµØ±ÙØŒ Ø§Ù„Ù†ØÙˆ ØŒ Ø§Ù„Ù…Ø¹Ù†Ù‰. ÙˆØ£Ù…Ø§ Ø§Ù„Ø£ØµÙˆØ§Øª ÙÙ‡ÙŠ Ø£Ø³Ø§Ø³ Ø§Ù„Ù„ØºØ©ØŒ ÙˆÙ„ÙƒÙ„ Ù„ØºØ© Â Ù†Ø¸Ø§Ù… ØµÙˆØªÙŠ Ø®Ø§Øµ ÙˆØ±Ù…ÙˆØ² Ø§ØµØ·Ù„Ø§ØÙŠØ©. Ù…Ù† Ø®Ù„Ø§Ù„ Ù‡Ø°Ø§ Ø§Ù„Ù†Ø¸Ø± Ø¥Ù„Ù‰ Ø¥Ù† Ø§Ù„Ù„ØºØ© Ø§Ù„Ø¹Ø±Ø¨ÙŠØ© Ù…Ù† Ø§Ù„Ø¹Ø§Ø¦Ù„Ø© Ø§Ù„Ù„ØºÙˆÙŠØ© Ø§Ù„Ø³Ø§Ù…ÙŠØ© ÙˆØ§Ù„ØªØ§Ù…Ù„ÙŠØ© Ù…Ù† Ù…Ø¬Ù…ÙˆØ¹Ø© Ø§Ù„Ù„ØºØ§Øª Ø§Ù„Ù‡Ù†Ø¯Ùˆ - Ø£ÙˆØ±ÙˆØ¨ÙŠØ©ØŒ ÙˆÙ…Ù…Ø§ Ù„Ø§Ø´Ùƒ ÙÙŠÙ‡ ÙŠØµØ¹Ø¨ Ø¹Ù„Ù‰ Ù…ØªØ¹Ù„Ù…ÙŠ Ø§Ù„Ù„ØºØ© Ø§Ù„Ø£Ø¬Ù†Ø¨ÙŠØ© ØªØØ¯ÙŠØ¯ Ù…Ø®Ø§Ø±Ø¬ Ø§Ù„Ø£ØµÙˆØ§Øª Ø§Ù„Ø¬Ø¯ÙŠØ¯Ø© ÙˆÙ†Ø·Ù‚Ù‡Ø§ ÙˆÙƒØªØ§Ø¨ØªÙ‡Ø§. ÙˆÙ…Ù†Ù‡Ù… Ø§Ù„Ù…Ø³Ù„Ù…ÙˆÙ† Ø§Ù„Ù†Ø§Ø·Ù‚ÙˆÙ† Ø¨Ø§Ù„Ù„ØºØ© Ø§Ù„ØªØ§Ù…Ù„ÙŠØ© Ø§Ù„Ø°ÙŠÙ† ÙŠØ³ØªØ®Ø¯Ù…ÙˆÙ† ÙˆÙŠØªØ¹Ù„Ù…ÙˆÙ† Ø§Ù„Ù„ØºØ© Ø§Ù„Ø¹Ø±Ø¨ÙŠØ© ÙƒÙ„ØºØ© Ø£Ø¬Ù†Ø¨ÙŠØ©ØŒ ÙÙ‡Ù… ÙŠÙˆØ§Ø¬Ù‡ÙˆÙ† Ø§Ù„Ù…Ø´Ù‚Ø© ÙÙŠ Ù†Ø·Ù‚ ÙˆÙƒØªØ§Ø¨Ø© Ø§Ù„ØØ±ÙˆÙ ÙˆØ§Ù„Ø£Ø¹Ù„Ø§Ù… ÙˆØ§Ù„Ù…ØµØ·Ù„ØØ§Øª Ø§Ù„Ø¹Ø±Ø¨ÙŠØ© Ù„Ø¹Ø¯Ù… Ø§Ù„ÙˆØ¶ÙˆØ ÙÙŠ Ø£ØµÙˆØ§Øª Ø§Ù„Ù„ØºØªÙŠÙ† Ø§Ù„Ø¹Ø±Ø¨ÙŠØ© ÙˆØ§Ù„ØªØ§Ù…Ù„ÙŠØ©. ÙØªØ±ÙƒØ²Øª Ù‡Ø°Ù‡ Ø§Ù„Ø¯Ø±Ø§Ø³Ø© ØªØØ¯ÙŠØ¯ Ø£ØµÙˆØ§Øª Ø§Ù„Ù„ØºØªÙŠÙ† Ø§Ù„Ø¹Ø±Ø¨ÙŠØ© ÙˆØ§Ù„ØªØ§Ù…Ù„ÙŠØ©ØŒ ÙˆØ§Ù„ÙƒØ´Ù Ø¹Ù† Ù…ÙˆØ§Ù‚Ø¹ Ø§Ù„Ø´Ø¨Ù‡ ÙˆØ§Ù„Ø®Ù„Ø§Ù Ø§Ù„ØµÙˆØªÙŠ Ø¨ÙŠÙ† Ø§Ù„Ù„ØºØªÙŠÙ†. Ø§Ø³ØªØ®Ø¯Ù…Øª Ù‡Ø°Ù‡ Ø§Ù„Ø¯Ø±Ø§Ø³Ø© Ø§Ù„Ù…Ù†Ù‡Ø¬ Ø§Ù„ÙˆØµÙÙŠ ÙˆØ§Ù„ØªÙ‚Ø§Ø¨Ù„ÙŠ Ù„ØªØÙ„ÙŠÙ„ Ø§Ù„Ù…Ø¹Ù„ÙˆÙ…Ø§Øª Ø§Ù„Ø«Ø§Ù†ÙˆÙŠØ© Ø§Ù„ØªÙŠ ØØµÙ„Øª Ø¹Ù„ÙŠÙ‡Ø§ Ù…Ù† Ø§Ù„Ø¯Ø±Ø§Ø³Ø§Øª Ø§Ù„Ø³Ø§Ø¨Ù‚Ø© ÙˆØ§Ù„ÙƒØªØ¨ ÙˆØ§Ù„Ù…Ø¬Ù„Ø§Øª ÙˆØ§Ù„Ù…Ù‚Ø§Ù„Ø§Øª ÙˆÙ…Ø§ØªØªØ¹Ù„Ù‚ Ø¨Ù‡Ø°Ø§ Ø§Ù„Ù…ÙˆØ¶ÙˆØ¹ Ù…Ù† Ø§Ù„Ø´Ø¨ÙƒØ§Øª Ø§Ù„Ø¥Ù„ÙƒØªØ±ÙˆÙ†ÙŠØ©. ÙˆÙÙŠ Ø®ØªØ§Ù… Ù‡Ø°Ù‡ Ø§Ù„Ø¯Ø±Ø§Ø³Ø© Ù‚Ø¯ ØØ¯Ø¯Øª Ø§Ù„Ø¨Ø§ØØ«Ø© Ù†ØªØ§Ø¦Ø¬ Ø´ØªÙ‰ØŒ ÙˆÙ…Ù†Ù‡Ø§:Â Ø¥Ù† Ø§Ù„ØØ±ÙˆÙ Ø§Ù„Ø¹Ø±Ø¨ÙŠØ© ØªØªÙ†Ø§ØØ± Ø¹Ù† Ø§Ù„ØØ±ÙˆÙ Ø§Ù„ØªØ§Ù…Ù„ÙŠØ© Ù…Ù† ØÙŠØ« Ø¹Ø¯Ø¯Ù‡Ø§ ÙˆØ·Ø±ÙŠÙ‚Ø© ÙƒØªØ§Ø¨ØªÙ‡Ø§ ÙˆØ§Ø®ØªÙ„Ø§Ù Ø£Ø´ÙƒØ§Ù„Ù‡Ø§ ØØ³Ø¨ Ø§Ù„Ù…ÙˆØ§Ù‚Ø¹ ÙÙŠ Ø§Ù„ÙƒÙ„Ù…Ø§Øª. ÙƒÙ…Ø§ Ø£Ù† ÙÙŠ Ø§Ù„Ù„ØºØ© Ø§Ù„Ø¹Ø±Ø¨ÙŠØ© Ø³ØªØ© Ø£ØµÙˆØ§Øª ØµØ§Ø¦ØªØ© ÙˆÙ‡ÙŠ ØªØªØ´Ø§Ø¨Ù‡ Ø³ØªØ© Ø£ØµÙˆØ§Øª ØµØ§Ø¦ØªØ© ÙÙŠ Ø§Ù„Ù„ØºØ© Ø§Ù„ØªØ§Ù…Ù„ÙŠØ© ØØ³Ø¨ Ø§Ù„Ù†Ø·Ù‚ ÙˆÙ„ÙƒÙ† Ù‡Ù†Ø§Ùƒ ØªÙ†Ø§ØØ±Ø§ Ø¨ÙŠÙ† ØµÙˆØ§Ø¦ØªÙ‡Ù…Ø§ Ù…Ù† ØÙŠØ« Ø§Ù„Ù…Ø®Ø±Ø¬ ÙˆØ§Ù„ØµÙØ©ØŒ ÙƒÙ…Ø§ Ø£Ù† Ø§Ù„ØµÙˆØ§Ù…Øª Ø§Ù„Ø¹Ø±Ø¨ÙŠØ© ØªØªÙ†Ø§ØØ± ÙƒØ«ÙŠØ±Ø§ Ø¹Ù† Ø§Ù„ØµÙˆØ§Ù…Øª Ø§Ù„ØªØ§Ù…Ù„ÙŠØ© Ù…Ù† ØÙŠØ« Ø§Ù„Ù†Ø·Ù‚ ÙˆØ§Ù„Ù…Ø®Ø§Ø±Ø¬ ÙˆØ§Ù„Ø±Ù…ÙˆØ² Ø§Ù„ØµÙˆØªÙŠØ© Ø§Ù„Ø¯ÙˆÙ„ÙŠØ© Ù„Ù‡Ø§. ÙˆØ¥Ù† Ù‡Ø°Ù‡ Ø§Ù„Ø¯Ø±Ø§Ø³Ø© ØªØ³Ø§Ø¹Ø¯ Ø¹Ù„Ù‰ Ø§Ù„Ù…Ø³Ù„Ù…ÙŠÙ† ÙˆØºÙŠØ± Ø§Ù„Ù…Ø³Ù„Ù…ÙŠÙ† Ø§Ù„Ù†Ø§Ø·Ù‚ÙŠÙ† Ø¨Ø§Ù„Ù„ØºØ© Ø§Ù„ØªØ§Ù…Ù„ÙŠØ© ÙÙŠ ØªØØ¯ÙŠØ¯ Ù†Ø·Ù‚ Ø§Ù„Ø£ØµÙˆØ§Øª Ø§Ù„Ø¹Ø±Ø¨ÙŠØ© ÙˆÙ‚Ø±Ø§Ø¡Ø© Ø§Ù„Ù„ØºØ© Ø§Ù„Ø¹Ø±Ø¨ÙŠØ© Ø¨Ø£ØØ³Ù† ÙˆØ¬Ù‡ ÙÙŠ Ø§Ù„Ù…Ø³ØªÙ‚Ø¨Ù„ Ø¨ÙˆØ§Ø³Ø·Ø© Ø§Ù„ÙˆØ¶ÙˆØ Ø¨ÙŠÙ† Ø£ØµÙˆØ§Øª Ù‡ØªÙŠÙ† Ø§Ù„Ù„ØºØªÙŠÙ†.Â Â Â